An update on the antibiotic-based root canal irrigation solutions - Mohammadi, Zahed (Iranian Endodontic Journal, 2008)
Abstract: Antibiotics are a valuable addition to health practitioners for the management of bacterial infections. During endodontic treatment and when managing trauma to the teeth, antibiotics may be applied systemically or locally. Due to the potential risk of adverse effects of systemic applications, and the ineffectiveness of systemic prescribed antibiotics in necrotic or pulpless teeth and the periradicular tissues, the local application of antibiotics may be a more effective mode for delivering antibiotics to infected root canals. The purpose of this article is to review the history, rationale, and applications of antibiotics and antibiotic-containing irrigants in endodontics.